2019
DOI: 10.1002/bio.3753
|View full text |Cite
|
Sign up to set email alerts
|

Micellar‐based spectrofluorimetric method for the selective determination of ledipasvir in the presence of sofosbuvir: application to dosage forms and human plasma

Abstract: A fast, low-cost, sensitive, and selective spectrofluorimetric method for the determination of ledipasvir was developed and validated. The method is based on an enhancement in the native fluorescence intensity of ledipasvir by 500% of its original value by the formation of hydrogen bonds between the cited drug and Tween-20 in the micellar system (pH = 5.0). All fluorescence measurements were carried out at 425 nm and 340 nm for emission and excitation wavelengths, respectively. A linear relationship between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In general, the micellar system creates a highly viscous environment that could limit the internal movement of the enclosed drug fluorophore to minimize the possibility of nonradiative deactivation process. [ 51 ] Electrostatic attraction occurs between the negatively charged anionic surfactant, SDS, and the positively charged DPH molecules (p K a of DPH is 8.98, the drug will be positively charged at pH 7 used during this study). This will produce a further limitation of the movement of DPH molecules and increase rigidity, leading to a great enhancement in fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the micellar system creates a highly viscous environment that could limit the internal movement of the enclosed drug fluorophore to minimize the possibility of nonradiative deactivation process. [ 51 ] Electrostatic attraction occurs between the negatively charged anionic surfactant, SDS, and the positively charged DPH molecules (p K a of DPH is 8.98, the drug will be positively charged at pH 7 used during this study). This will produce a further limitation of the movement of DPH molecules and increase rigidity, leading to a great enhancement in fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 44,45 ] As the calculated t ‐ (paired) and F‐values at the 95% confidence level were less than the tabulated values, it was concluded that no significant difference among the two methods was observed. In the interval hypothesis test, true bias based on recovery experiments was evaluated using the following equation [ 44 ] : θ2[]x12Sp0.5em2t2normaln12normalθx1x2+[]x22Sp0.5em2t2normaln2=0 Lower limit ( θ L ) and upper limit ( θ U ) of the confidence interval were obtained: lefttruenormalθU=b+b24ac2anormalθL=bnormalb24ac2a where, lefttruea=normalx12Sp2normalt2/normaln1b=2normalx1x2c=normalx22Sp2normalt2/normaln2 where x 1 and x 2 are mean values determined by the proposed and the reported methods, respectively. S p and t are the pooled standard deviation and one‐sided t ‐value at the 95% confidence level, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The utilization of surfactants has a positive impact on analysis with respect to improvement or induction of fluorescence in addition to chromatographic resolution. [21][22][23][24][25][26] SDS above its critical micellar concentration (CMC) has shown improved sensitivity in this research work. The developed methods have numerous advantages such as being very simple without tedious sample pretreatment or analysis steps using available inexpensive solvents (distilled water or SDS) compared to Britton Robinson buffer and pH adjustment in reported spectroflourimetric method [20] and the sophisticated steps required for chromatographic or electrochemical analysis [9][10][11][12][13][14][15] that need well-trained personnel.…”
Section: Introductionmentioning
confidence: 99%